Kinetics of Polymerization of Some Vinyl Monomers by Mn(III)-Aspartic Acid Redox System - Shanmuga Sundari, S.; Subbu, S. (Asian Journal of Chemistry, 2010)
The polymerization of acrylamide, acrylic acid and methyl acrylate initiated by Mn(III)-aspartic acid redox system in aqueous sulphuric acid has been studied. The influence of [monomer], [Mn(III) ion], [aspartic acid], [H+] and ionic strength of medium on the rates of polymerization and Mn(III) ion disappearance has been investigated. The effect of temperature on the rate of polymerization has been studied in the range of 298-318 K and the thermodynamic quantities have been evaluated. A suitable mechanism consistent with the kinetic results has been proposed. The rate coefficients (ki/k0) of the monomers are calculated and their reactivities are compared.